Encapsulation of DHA oils for better bioavailability: A review from the practical aspect - Jala, Ram Chandra Reddy; Zhang, Hong; Yang, Ming; Guo, Ruihua; Li, Sheng; Xu, Xiaolan; Yang, Dongying; Xu, Xuebing (Journal of the American Oil Chemists' Society, 2025)
DHA has unique functional properties in human health. Various recommendations to increase dietary intake have been proposed. However, there is a difference between intake and nutritional functions. Therefore, bioavailability is crucial for the efficacy of DHA intake. A proper delivery system can increase the bioavailability up to 50%–150%. DHA in phospholipid and triglyceride forms is readily absorbed by the body more than in ethyl ester form. DHA oil encapsulation can attain better bioavailability, controlled release, and masking of taste and odor, besides improving the oxidative stability. The encapsulation is the formation of a matrix in which the DHA oil is hidden inside the wall materials. Wall materials such as whey protein concentrates are often preferred, and multiple layers through molecular assembly are often pursued. In Forming the right matrix, emulsification technologies are applied to have the designed matrix where nanoemulsion or liposome‐type structures have advantages. For an encapsulated powder product, spray drying or developed alternative techniques give large space for improvement, in which novel developments such as spray–freeze drying may offer various advantages. This review will bring a practical picture of the subject including an overall evaluation of patent applications as well as a summary/remarks of the future developments.